Geographical variation and taxonomy of the snail-eating snake Dipsas albifrons (Sauvage, 1884), with comments on the systematic status of Dipsas albifrons cavalheiroi Hoge, 1950 (Serpentes: Colubridae: Dipsadinae) - Passos, Paulo; Fernandes, Ronaldo; Porto, Marcovan (Zootaxa, 2005)
The taxonomic status of Dipsas albifrons is revised and geographic variation of external morphology and hemipenis are described. Multivariate analyses suggest that the pattern of geographical variation is correlated with gap sampling, probably indicating a northernward cline in segmental counts (mainly ventral and subcaudal scales). Quantitative and qualitative analyses reveal that the island population (Dipsas albifrons cavalheiroi) is not divergent from mainland populations and, herein, is considered a junior synonymy of Dipsas albifrons. A lectotype of Dipsas albifrons is designated.